Amino acid substitutions contributing to α2, 6‐sialic acid linkage binding specificity of human parainfluenza virus type 3 hemagglutinin–neuraminidase. Issue 11 (11th April 2015) - Fukushima, Keijo; Takahashi, Tadanobu; Ueyama, Hiroo; Takaguchi, Masahiro; Ito, Seigo; Oishi, Kenta; Minami, Akira; Ishitsubo, Erika; Tokiwa, Hiroaki; Takimoto, Toru; Suzuki, Takashi
Abstract : Human parainfluenza virus type 3 (hPIV3) recognizes both α2, 3‐ and α2, 6‐linked sialic acids, whereas human parainfluenza virus type 1 (hPIV1) recognizes only α2, 3‐linked sialic acids. To identify amino acid residues that confer α2, 6‐linked sialic acid recognition of hPIV3, amino acid residues in or neighboring the sialic acid binding pocket of the hPIV3 hemagglutinin–neuraminidase (HN) glycoprotein were substituted for the corresponding residues of hPIV1 HN. Hemadsorption assay with sialyl linkage‐modified red blood cells indicated that amino acid residues at positions 275, 277, 372, and 426 contribute to α2, 6‐linked sialic acid recognition of the HN3 glycoprotein. Abstract : Alpha2, 6‐linked sialic acid recognition of hPIV3 is dependent on HN. Four amino acid positions on HN contribute to the recognition. The recognition may be related to the higher pathogenicity of hPIV3.